Eimeria bovis Macromeront Formation Induces Glycolytic Responses and Mitochondrial Changes in Primary Host Endothelial Cells - Velásquez, Zahady D.; López-Osorio, Sara; Mazurek, Sybille; Hermosilla, Carlos; Taubert, Anja (Frontiers in Cellular and Infection Microbiology, 2021)
Eimeria bovis is an intracellular apicomplexan parasite that causes considerable economic losses in the cattle industry worldwide. During the first merogony, E. bovis forms large macromeronts with >140,000 merozoites I in host endothelial cells. Because this is a high-energy demanding process, E. bovis exploits the host cellular metabolism to fulfill its metabolic requirements. We here analyzed the carbohydrate-related energetic metabolism of E. bovis–infected primary bovine umbilical vein endothelial cells during first merogony and showed that during the infection, E. bovis–infected culture presented considerable changes in metabolic signatures, glycolytic, and mitochondrial responses. Thus, an increase in both oxygen consumption rates (OCR) and extracellular acidification rates (ECAR) were found in E. bovis–infected host cells indicating a shift from quiescent to energetic cell status. Enhanced levels of glucose and pyruvate consumption in addition to increased lactate production, suggesting an important role of glycolysis in E. bovis–infected culture from 12 days p.i. onward. This was also tested by glycolytic inhibitors (2-DG) treatment, which reduced the macromeront development and diminished merozoite I production. As an interesting finding, we observed that 2-DG treatment boosted sporozoite egress. Referring to mitochondrial activities, intracellular ROS production was increased toward the end of merogony, and mitochondrial potential was enhanced from 12 d p. i. onward in E. bovis–infected culture. Besides, morphological alterations of membrane potential signals also indicated mitochondrial dysfunction in macromeront-carrying host endothelial culture.